Regional-Scale Analysis of Antimicrobial Usage in Smallholder Cattle Herds (Aosta Valley, Italy): Why Surveillance Matters - Federico Scali; Sandra Ganio; Claudio Roullet; Mauro Ruffier; Stefania Bergagna; Giulia Pagliasso; Claudia Romeo; Nicoletta Formenti; Antonio Marco Maisano; Giovanni Santucci; Matteo Tonni; Federica Guadagno; et al. (MDPI AG, 2024)
Optimising antimicrobial usage (AMU) in livestock is pivotal to counteract the emergence of antimicrobial resistance. We analysed AMU in more than 1000 cattle herds over 11 years (2008-2018) in the Aosta Valley (Italy), a region where 80% of farms house less than 50 cattle. Dairy cows accounted for over 95% of AMU. AMU was estimated using the defined daily dose animal for Italy (DDDAit) per biomass for the whole herd and a treatment incidence 100 (TI100) for cows. Average annual herd-level AMU was low, with 3.6 DDDAit/biomass (range: 3.2-4.0) and 1.2 TI100 in cows (range: 1.1-1.3). Third and fourth generation cephalosporins, which are critical for human medicine, represented almost 10% of usage, and intramammary antimicrobials accounted for over 60%. We detected significant downward temporal trends in total AMU, as well as a positive relationship with herd size. The magnitude of such effects was small, leaving scant room for further reduction. However, the frequent use of critical antimicrobials and intramammary products should be addressed, following the principles of prudent AMU. Our findings highlight the importance of monitoring AMU even in low-production, smallholding contexts where a low usage is expected, to identify any deficiencies and implement interventions for further AMU optimisation.